PEREMPUAN BERSANGGUL NUSANTARA: PRAKTIK PEMBERDAYAAN MASYARAKAT BERBASIS PEMBELAJARAN MASYARAKAT ADAT DARI PERSPEKTIF KESETARAAN GENDER - Widyaswari, Monica; Fakhrudin, Ali; Oktavia, Elvira (LPPM Universitas Negeri Surabaya, 2024)
Perempuan Bersanggul Nusantara is a community of women who care about national development programs. One of the activities implemented to date is skills-based empowerment activities. This activity is intended to give women good skills where their potential can be developed. The development of women's potential is a manifestation of women's empowerment so that women are more qualified and can participate in development. The application of indigenous learning in empowerment by the Perempuan Bersanggul Nusantara community has its meaning, namely an application of learning about local culture and customary values that are attempted to increase appreciation for the practice of daily activities. The approach used in this study is qualitative with a case study method. The study subjects were the Perempuan Bersanggul Nusantara community and women (adolescents and adults). Data collection techniques used in-depth interviews, participatory observation, and documentation studies. Data analysis techniques used the Miles and Huberman interactive model. The results of this study are (a) Perempuan Bersanggul Nusantara reviewed in the Socio-Cultural Context; (b) Indigenous Learning in Women's Empowerment in the Perempuan Bersanggul Nusantara Community; (c) Gender Equality Perspective in Perempuan Bersanggul Nusantara.